The Gulf of St. Lawrence Biogeochemical Model: A Modelling Tool for Fisheries and Ocean Management - Lavoie, Diane; Lambert, Nicolas; Starr, Michel; Chassé, Joël; Riche, Olivier; Le Clainche, Yvonnick; Azetsu-Scott, Kumiko; Béjaoui, Béchir; Christian, James R.; Gilbert, Denis (Frontiers in Marine Science, 2021)
The goal of this paper is to give a detailed description of the coupled physical-biogeochemical model of the Gulf of St. Lawrence that includes dissolved oxygen and carbonate system components, as well as a detailed analysis of the riverine contribution for different nitrogen and carbonate system components. A particular attention was paid to the representation of the microbial loop in order to maintain the appropriate level of the different biogeochemical components within the system over long term simulations. The skill of the model is demonstrated using in situ data, satellite data and estimated fluxes from different studies based on observational data. The model reproduces the main features of the system such as the phytoplankton bloom, hypoxic areas, pH and calcium carbonate saturation states. The model also reproduces well the estimated transport of nitrate from one region to the other. We revisited previous estimates of the riverine nutrient contribution to surface nitrate in the Lower St. Lawrence Estuary using the model. We also explain the mechanisms that lead to high ammonium concentrations, low dissolved oxygen, and undersaturated calcium carbonate conditions on the Magdalen Shallows.